Debt-GDP cycles in historical perspective: the case of the USA (1889–2014). (20th September 2022) - Stockhammer, Engelbert; Gouzoulis, Giorgos
Abstract: Since the Global Financial Crisis, interest in financial cycles has risen significantly. While much of modern macroeconomics conceives financial crises as the results of exogenous shocks, Minsky's financial instability hypothesis posits that financial cycles are endogenous to the economic system. The main contribution of this paper is to use historical macroeconomic data for the United States (1889–2014) to econometrically test for endogenous Minsky cycles: the interaction of procyclical private debt-to-income ratios and a dampening effect of private debt on economic activity. We analyze corporate debt-gross domestic product (GDP) growth cycles, which feature in Minsky's original writings, and mortgage debt-GDP growth cycles as in some recent Minsky-inspired models. We find robust evidence of endogenous corporate debt-GDP cycles over the last 125 years. These results are driven by the pre-World War II (WWII), and post-1973 periods, which had a more liberal economic policy orientation. We find no evidence of mortgage debt-GDP cycles.